The effect of payment medium on effort. - Incekara‐Hafalir, Elif; Kumar, Raymond; Silva‐Goncalves, Juliana (Economic Inquiry, 2022)
Employers reward workers and researchers pay human subjects using different payment mediums. These payment mediums can have various psychological effects on workers/research participants, and thereby influence their effort provision. In this paper, we investigate the effect of payment medium on participants' effort in a lab experiment. We find evidence that payment mediums affect participants' productivity when a fixed payment scheme is used, but not under a performance‐based payment scheme.